Emoji of “Thumbs up” as confirmation of a Contract - Ventura Zurita, José Jhordy (2024)
In this jurisprudential commentary, the contractual dispute between South West Terminal and Achter Land & Cattle is analyzed, where the interpretation of a "thumbs up" emoji as confirmation of a contract is debated. The court concluded that an emoji can be interpreted as a valid confirmation of a contract, provided there is clear and consistent context supporting this interpretation.